DESIGNING SOLAR POWER SYSTEM FOR OFFSHORE PLATFORM - Mohammad, Fadhila (Universiti Teknologi PETRONAS, 2007)
A solar power system is designed for offshore platform in order to supply power to DC loads such as emergency lighting, VHF radio, remote terminal unit, well head control panel, multiphase flow meter, fire and gas panel, marine lantern, and fog horn system. In this project, the main objective is to design, analyze and sizing the solar power system for DC loads at offshore platform. This project will be beneficial for oil and gas industries in installing their offshore platform because by using the solar power system, they can actually reduce the cost of the project in terms of supplying the DC power. A study concerning the economics of solar versus generators as a choice of power was conducted. The study considers all costs involved: modules, mounting structure, pumps, miscellaneous components, installation, operation, maintenance, yearly inspection, component replacement and salvagevalue. The study concludes that, the use of solar power is more reliable in terms of cost and minimum environment impact. The solar power system will be installed at a new rriinimum facilities wellhead platform. A common perception about solar energy is that it is expensive, but it is just the installation cost that is quite higher compared to others power supply. Foran investment thatwill last for twenty years or more, solar power systems are very cost effective. There is almost no running cost and the replacement costs of some equipments such as batteries only occurs once in every fewyears. The concern is not only in solar panel, but includes battery storage system. The project is completed bydesigning, choosing, calculating and verifying the designed systems.